Comparation of flow calculations using the population load coefficient method and population distribution by individual sections of the water supply network (Proceedings of Faculty of Civil Engineering, 2024)
The paper presents a comparison and analysis of the flow calculation using the population load coefficient method K and population distribution by individual sections of the branched water supply network. The hydraulic design is based on the laid water supply network for the community of Ližnjan in Istria. Using the population coefficient load method K, a characteristic section of the water supply network is defined, and then the population load coefficient is defined for the remaining sections. After that, the virtual lengths and specific flow for sections of the water supply network are defined in l/s/m, based on which the own flows for individual sections of the water supply network are calculated. The second method defines the number of inhabitants on individual sections of the water supply network, based on which the specific flow for sections of the water supply network is defined in l/s/inhab. After that, own flows are calculated for individual sections of the water supply network. Hydraulic design is made based on the calculated total flows covered by the given methods, and also the comparison and analysis of total flows, pipe diameters, velocities and pressures on individual sections and nodes of the water supply network is given. The conducted comparisons of hydraulic calculations did not reveal any significant differences in the flows, and therefore not in the pipe diameters and velocities in individual sections of the system, nor in the pressures calculated in the calculation nodes of the water supply network. When used properly, both methods give reliable results.
Keywords: water supply network; specific flow; hydraulic design; population load coefficient; own flow; pipe diameter; pressure; velocity